Potassium Periodate Mediated Oxidative Cyclodesulfurization toward Benzofused Nitrogen Heterocycles - Chuthamat Duangkamol (2020)
© 2020 Georg Thieme Verlag. All rights reserved. A convenient oxidative cyclodesulfurization method toward the synthesis of benzofused nitrogen heterocycles using inexpensive and readily available potassium periodate as an oxidant was developed. Upon treating isothiocyanates with ortho -substituted anilines bearing N, N -, N, O -, and N, S -bis-nucleophiles, followed by an intramolecular cyclization of the in situ generated monothioureas, substituted 2-aminobenzazole series were rapidly accessible in good to excellent yields. The protocol can accommodate various substituents on both substrates while allowing more efficient, greener, and operational simpler process relative to other oxidative coupling reactions. Tetracyclic quinazolinone derivatives were also afforded in high yields in a single preparative step and chromatography-free.